A high-strength laminated glass based on an intermediate film and a preparation method thereof
By introducing reactive anti-ultraviolet agents, starch nanoparticles and chain extenders into the intermediate film of the laminated glass, the crosslinking network is regulated, and the problem of insufficient water absorption and impact resistance of the intermediate film in the prior art is solved, and a laminated glass with high strength, excellent anti-ultraviolet and aesthetics is achieved.
Patent Information
- Application Number
- CN202411119348.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The polyvinyl butyral and polyurethane intermediate films used in existing laminated glasses have shortcomings in water absorption and impact resistance, and the introduction of anti-ultraviolet agents will affect the transparency and adhesion of the intermediate layer.
By introducing reactive anti-ultraviolet agents, starch nanoparticles and chain extenders, the crosslinking network of the polyurethane intermediate film is regulated, its tensile strength, adhesion and UV radiation resistance are improved, and adhesion and mechanical properties are improved through solvent modification treatment.
On the basis of ensuring transparency of more than 80%, the tensile strength, adhesion and UV radiation resistance of the intermediate film are significantly improved, thereby improving the comprehensive performance of laminated glass, including impact resistance and aesthetics.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laminated glass, in particular to a high-strength laminated glass based on an intermediate film and a preparation method thereof. Background Art
[0002] Laminated glass (safety glass) is a composite glass product made of a polymer interlayer and glass arranged on both sides of the interlayer through high temperature pressing. It is widely used in various fields such as construction and transportation. Among them, the polymer interlayer plays an important and decisive role. At present, polyvinyl butyral is usually used as an interlayer in laminated glass. Although it has advantages such as good transparency and adhesion, its water absorption will reduce the safety of laminated glass, and its impact resistance is generally not enough to withstand strong external impact.
[0003] Polyurethane is also a polymer with transparency, adhesion and controllability, and is expected to become a potential material for intermediate films. However, using polyurethane as an intermediate film also has the advantages of high transparency and high and low temperature resistance; but its tensile strength and adhesion still need to be further improved to improve its applicability in laminated glass, thereby enhancing the impact resistance and bonding properties of laminated glass. On the other hand, since safety glass is usually used in curtain walls or windshields, its UV resistance needs to be further improved; however, the introduction of UV inhibitors usually has compatibility and migration, which leads to a decrease in the transparency, adhesion and other properties of the intermediate layer, thereby affecting the performance of laminated glass.
[0004] In summary, it is of great significance to prepare a high-strength laminated glass based on an intermediate film using polyurethane as the main material of the intermediate film. Summary of the invention
[0005] The object of the present invention is to provide a high-strength laminated glass based on an intermediate film and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing high-strength laminated glass based on an intermediate film comprises the following steps:
[0008] Step 1: Add polytetramethylene glycol and reactive UV-resistant agent to N,N-dimethylformamide in sequence; add diisocyanate and organotin catalyst in sequence under nitrogen atmosphere; heat to 80-85°C for reaction for 2-3 hours; vacuum degassing; add starch dispersion containing starch nanoparticles, stir for 20-30 minutes under ultraviolet light; add chain extender and reactive dye, stir for 20-30 minutes; pour into a mold, cure at 75-85°C for 1.5-2.5 days; let stand at room temperature for 4-6 days to obtain an intermediate film;
[0009] Step 2: Soak the interlayer in toluene for 6 to 10 hours, transfer to methanol and soak for 2 to 4 hours; dry at room temperature for 3 to 5 days to obtain a modified interlayer;
[0010] Step 3: Place the modified interlayer film between two layers of glass and heat-press them to obtain high-strength laminated glass.
[0011] More optimally, the raw materials of the intermediate film include the following components: by weight, 18 to 22 parts of polytetramethylene ether diol, 2 to 3 parts of reactive UV inhibitors, 11 to 13 parts of diisocyanates, 0.5 to 1 parts of organic tin catalysts, 1 to 1.5 parts of starch nanoparticles, 1 to 2 parts of chain extenders, and 0.5 to 1 parts of reactive dyes.
[0012] More optimally, the preparation method of the reactive UV inhibitor is as follows: (1) uniformly stirring citric acid, cysteine and deionized water, stirring at 75-80°C for 2-2.5 hours; transferring to a blast oven, drying at 130-140°C for 10-12 hours to obtain pyridone diacid; (2) uniformly mixing pyridone diacid, epichlorohydrin and tetrabutylammonium bromide, stirring at 80-85°C for 20-30 minutes; cooling to 45-50°C, adding sodium hydroxide solution dropwise, stirring for 20-30 minutes; heating to 52-55°C and stirring for 4-6 hours; obtaining diepoxy pyridone; (3) sequentially adding diepoxy pyridone and 2-(vinyloxy)ethylamine to toluene, reacting at 60-65°C for 6-8 hours, and evaporating toluene to obtain a reactive UV inhibitor.
[0013] More optimally, the mass ratio of the citric acid, cysteine and deionized water is 19:(12-15):(10-20); the mass ratio of the pyridone diacid and epichlorohydrin is 3:(20-22); and the molecular weight of the diepoxypyridone and 2-(ethyleneoxy)ethylamine is 4:(2.8-3).
[0014] More optimally, the starch dispersion includes the following raw materials: 1-1.5 wt% starch nanoparticles, 0.05-0.08 wt% photoinitiator, and the rest is N,N-dimethylformamide.
[0015] More optimally, the preparation method of the starch nanoparticles is as follows: (1) mixing thioglycolic acid, acetic anhydride and corn starch uniformly, adding sulfuric acid, stirring and reacting at room temperature for 12 to 16 hours; washing and drying to obtain thiolated starch; (2) dispersing corn starch and thiolated starch in a mass ratio of 4:1 in deionized water in turn to obtain a solution with a solid content of 5 to 6 wt%; stirring the solution at 90 to 92° C. for 1 to 1.5 hours, setting the power to 550 to 600 W for ultrasonic treatment for 10 to 15 minutes; centrifuging and taking the supernatant; (3) in an ice bath, setting the power of ultrasound to 550 to 600 W, transferring the supernatant to anhydrous ethanol at a rate of 2 to 5 mL / min, centrifuging and drying to obtain starch nanoparticles.
[0016] More optimally, the chain extender comprises 1,4-butanediol and 2,6-pyridine dimethanol in a mass ratio of 3:2.
[0017] Preferably, the UV irradiation process is performed at a light irradiance of 20 to 50 mW / cm 2 .
[0018] More optimally, the temperature of the hot pressing composite is 120-140° C., the pressure is 0.4-0.6 MPa, and the time is 3-8 min.
[0019] More optimally, a high-strength laminated glass prepared by a preparation method of a high-strength laminated glass based on an intermediate film, in which the thickness of the intermediate film is 0.2±0.05 mm.
[0020] Compared with the prior art, the beneficial effects of the present application are as follows: in the scheme, by introducing reactive UV-resistant agents, starch nanoparticles and limited chain extenders, the cross-linked network of polyurethane in the intermediate film is effectively regulated, thereby effectively enhancing the tensile strength, adhesion and UV resistance of the intermediate film while ensuring a transparency greater than 80%, thereby improving the comprehensive performance of laminated glass.
[0021] (1) Pyridone diacid is prepared by reacting citric acid and cysteine, and the heterocyclic ring contained in it has anti-ultraviolet properties; in order to improve its compatibility and inhibit the migration of small molecules; in the scheme, pyridone diacid is further grafted with epoxy groups by reacting carboxyl groups and chlorine; and then 2-(vinyloxy)ethylamine is grafted by the reaction of epoxy groups and amino groups to obtain a reactive anti-ultraviolet agent; wherein, the epoxy groups and amino groups open the ring to produce hydroxyl groups, which can act as diol grafting blocks in polyurethane. Due to the presence of heterocyclic rings, the tensile strength and anti-ultraviolet properties of polyurethane are improved. In this way, the dispersibility of the anti-ultraviolet agent in the intermediate film layer is effectively increased, and the negative impact is suppressed. On the other hand, the grafted 2-(vinyloxy)ethylamine contains alkenyl groups, which is conducive to the dispersibility of subsequent starch nanoparticles in the intermediate film. This addition effectively enhances the anti-ultraviolet and impact resistance of laminated glass. In addition, in the scheme, 2,6-pyridine dimethanol containing pyridine groups is further introduced into the subsequent chain extender to further improve the overall performance.
[0022] (2) Starch nanoparticles are introduced into the scheme, and there are molecular interactions with the rest of the polyurethane. Starch nanoparticles can serve as a reinforcing phase to improve the strength and adhesion of the polyurethane type interlayer, thereby improving the impact resistance of the laminated glass. The introduction of starch nanoparticles will increase the hydrogen bonding degree of the polyurethane type interlayer and increase its tensile strength. The use of olefin-grafted starch nanoparticles in the reactive UV inhibitor in the polyurethane can increase the orderliness of the starch nanoparticles in the cross-linked network of the polyurethane type interlayer, forming an ordered microphase separation structure, thereby ensuring that the transmittance is greater than 80% and increasing the mechanical properties.
[0023] (3) Since the amount of reactive UV-resistant agent and starch nanoparticles introduced should not be too much, as too much is detrimental to the mechanical properties, in the scheme, the intermediate film is further modified by using a solvent. The solvent is infiltrated on the surface of the intermediate film to expand the intermediate film, increase the space and activity in the molecular chain, rearrange the hydrogen bonds, and promote the increase of the hydrogen bonding degree in the chain segment. Then the solvent evaporates to form disordered hydrogen bonds. This is then hot-pressed between the two layers of glass to increase the adhesion and mechanical properties, thereby further improving the impact resistance of the laminated glass.
[0024] (4) In addition, a reactive dye is introduced into the intermediate film layer, which is generally a Yetta polymer reactive dye having multiple hydroxyl groups that can react with isocyanate, thereby increasing the color of the laminated glass and further increasing the aesthetics of the laminated glass. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] It should be noted that the number of parts in the specific implementation manner is by mass; the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and are exemplified as follows: in the following embodiments, the model of the reactive dye is EVERTINT Red R-01, and the brand is Yongguang; the purity of corn starch is 98%, the model is KA741214, and the brand is Jieshikai; the model of polytetramethylene ether diol is PTMEG650, the model of the organic tin catalyst is T-9, the CAS number of isophorone diisocyanate is 16672-87-0, the CAS number of 1,4-butanediol is 110-63-4, and the CAS number of 2,6-pyridine dimethanol is 1195-59-1, all of which are commercially available.
[0027] The preparation method of the reactive UV inhibitor is as follows: (1) 19 parts of citric acid, 12.5 parts of cysteine and 15 parts of deionized water are uniformly stirred and stirred at 80°C for 2 hours; the mixture is transferred to a blast oven and dried at 140°C for 12 hours to obtain pyridone diacid; (2) 30 parts of pyridone diacid, 200 parts of epichlorohydrin and 1.7 parts of tetrabutylammonium bromide are uniformly mixed and stirred at 80°C for 30 minutes; the mixture is cooled to 50°C, 5 parts of 10 wt% sodium hydroxide solution are added dropwise and stirred for 30 minutes; the mixture is heated to 55°C and stirred for 6 hours to obtain diepoxy pyridone; (3) 40 parts of diepoxy pyridone and 28 parts of 2-(vinyloxy)ethylamine are added to 200 parts of toluene in sequence, the mixture is reacted at 60°C for 8 hours, and the toluene is evaporated to obtain the reactive UV inhibitor.
[0028] The preparation method of starch nanoparticles is as follows: (1) 10 parts of thioglycolic acid, 4.2 parts of acetic anhydride and 2 parts of corn starch are mixed evenly, 0.1 parts of sulfuric acid are added, the mixture is stirred at room temperature for 12 hours, the supernatant is discarded, the mixture is washed with ethanol, and vacuum dried at 40°C to obtain thiolated starch; (2) corn starch and thiolated starch are dispersed in deionized water in a mass ratio of 4:1 to obtain a solution with a solid content of 5 wt%; the solution is stirred at 90°C for 1 hour, ultrasonically treated at a power of 600 W for 10 minutes, centrifuged and the supernatant is taken; (3) in an ice bath, the ultrasonic wave is set at a power of 600 W, the supernatant is transferred to 100 parts of anhydrous ethanol at a rate of 5 mL / min, the solution is centrifuged, the precipitate is washed with cold water, and freeze-dried to obtain starch nanoparticles.
[0029] Embodiment 1: A method for preparing high-strength laminated glass based on an intermediate film, comprising the following steps:
[0030] Step 1: 20 parts of polytetramethylene glycol and 2 parts of reactive UV inhibitor were added to N, N-dimethylformamide in sequence; 12 parts of isophorone diisocyanate and 0.8 parts of organic tin catalyst were added in sequence under nitrogen atmosphere; the temperature was raised to 85°C for reaction for 2 hours; vacuum degassing was performed; 1.2 parts of starch dispersion containing starch nanoparticles (1.2wt% starch nanoparticles, 0.05wt% photoinitiator benzoin dimethyl ether, and the rest N, N-dimethylformamide) were added, and the light irradiance was 40mW / cm 2 Under ultraviolet light, stir for 20 minutes; add 1.8 parts of chain extender (1,4-butanediol and 2,6-pyridine dimethanol with a mass ratio of 3:2) and 0.5 parts of reactive dye, stir for 20 minutes; pour it into a mold and cure it at 80°C for 2 days; let it stand at room temperature for 5 days to obtain a 0.2mm intermediate film;
[0031] Step 2: Soak the interlayer in toluene for 8 hours, transfer it to methanol and soak it for 4 hours; dry it at room temperature for 4 days to obtain a modified interlayer;
[0032] Step 3: Place the modified interlayer film between two layers of glass, set the temperature to 140°C, the pressure to 0.5 MPa, and perform hot pressing for 5 minutes to obtain high-strength laminated glass.
[0033] Embodiment 2: A method for preparing high-strength laminated glass based on an intermediate film, comprising the following steps:
[0034] Step 1: 18 parts of polytetramethylene glycol and 2 parts of reactive UV inhibitor were added to N, N-dimethylformamide in sequence; under nitrogen atmosphere, 11 parts of isophorone diisocyanate and 0.5 parts of organic tin catalyst were added in sequence; the temperature was raised to 85°C for reaction for 2 hours; vacuum degassing was performed; a starch dispersion containing 1.5 parts of starch nanoparticles (1.5wt% starch nanoparticles, 0.05wt% photoinitiator benzoin dimethyl ether, and the rest was N, N-dimethylformamide) was added, and the mixture was stirred at a light irradiance of 40mW / cm 2 Under ultraviolet light, stir for 20 minutes; add 2 parts of chain extender (1,4-butanediol and 2,6-pyridine dimethanol with a mass ratio of 3:2) and 0.5 parts of reactive dye, stir for 20 minutes; pour it into a mold and cure it at 80°C for 2 days; let it stand at room temperature for 5 days to obtain a 0.2mm intermediate film;
[0035] Step 2: Soak the interlayer in toluene for 10 hours, transfer to methanol and soak for 2 hours; dry at room temperature for 5 days to obtain a modified interlayer;
[0036] Step 3: Place the modified interlayer film between two layers of glass, set the temperature to 140°C, the pressure to 0.5 MPa, and perform hot pressing for 5 minutes to obtain high-strength laminated glass.
[0037] Embodiment 3: A method for preparing high-strength laminated glass based on an intermediate film, comprising the following steps:
[0038] Step 1: 22 parts of polytetramethylene glycol and 3 parts of reactive UV inhibitor were added to N, N-dimethylformamide in sequence; under nitrogen atmosphere, 13 parts of isophorone diisocyanate and 1 part of organic tin catalyst were added in sequence; the temperature was raised to 85°C for reaction for 2 hours; vacuum degassing was performed; a starch dispersion containing 1 part of starch nanoparticles (1wt% starch nanoparticles, 0.05wt% photoinitiator benzoin dimethyl ether, and the rest was N, N-dimethylformamide) was added, and the light irradiance was 40mW / cm 2 Under ultraviolet light, stir for 20 minutes; add 1 part of chain extender (1,4-butanediol and 2,6-pyridine dimethanol with a mass ratio of 3:2) and 0.5 parts of reactive dye, stir for 20 minutes; pour it into a mold and cure it at 80°C for 2 days; let it stand at room temperature for 5 days to obtain a 0.2mm intermediate film;
[0039] Step 2: Soak the interlayer in toluene for 6 hours, transfer it to methanol and soak it for 4 hours; dry it at room temperature for 4 days to obtain a modified interlayer;
[0040] Step 3: Place the modified interlayer film between two layers of glass, set the temperature to 140°C, the pressure to 0.5 MPa, and perform hot pressing for 5 minutes to obtain high-strength laminated glass.
[0041] Comparative Example 1: A method for preparing high-strength laminated glass based on an intermediate film, without introducing a reactive anti-ultraviolet agent; the rest is the same as Example 1; specifically comprising the following steps:
[0042] Step 1: 22 parts of polytetramethylene glycol were added to N, N-dimethylformamide in sequence; under nitrogen atmosphere, 12 parts of isophorone diisocyanate and 0.8 parts of organic tin catalyst were added in sequence; the temperature was raised to 85°C for reaction for 2 hours; vacuum degassing was performed; 1.2 parts of starch dispersion containing starch nanoparticles (1.2wt% starch nanoparticles, 0.05wt% photoinitiator benzoin dimethyl ether, and the rest was N, N-dimethylformamide) was added, and the mixture was stirred at a light irradiance of 40mW / cm 2 Under ultraviolet light, stir for 20 minutes; add 1.8 parts of chain extender (1,4-butanediol and 2,6-pyridine dimethanol with a mass ratio of 3:2) and 0.5 parts of reactive dye, stir for 20 minutes; pour it into a mold and cure it at 80°C for 2 days; let it stand at room temperature for 5 days to obtain a 0.2mm intermediate film;
[0043] Step 2: Soak the interlayer in toluene for 8 hours, transfer it to methanol and soak it for 4 hours; dry it at room temperature for 4 days to obtain a modified interlayer;
[0044] Step 3: Place the modified interlayer film between two layers of glass, set the temperature to 140°C, the pressure to 0.5 MPa, and perform hot pressing for 5 minutes to obtain high-strength laminated glass.
[0045] Comparative Example 2: A method for preparing high-strength laminated glass based on an intermediate film, wherein 2,6-pyridine dimethanol is used to replace a reactive anti-ultraviolet agent; specifically comprising the following steps:
[0046] Step 1: 20 parts of polytetramethylene glycol and 2 parts of 2,6-pyridine dimethanol were added to N,N-dimethylformamide in sequence; under nitrogen atmosphere, 12 parts of isophorone diisocyanate and 0.8 parts of organic tin catalyst were added in sequence; the temperature was raised to 85°C for reaction for 2 hours; vacuum degassing was performed; a starch dispersion containing 1.2 parts of starch nanoparticles (1.2wt% starch nanoparticles, 0.05wt% photoinitiator benzoin dimethyl ether, and the rest was N,N-dimethylformamide) was added, and the irradiance was 40mW / cm 2 Under ultraviolet light, stir for 20 minutes; add 1.8 parts of chain extender (1,4-butanediol and 2,6-pyridine dimethanol with a mass ratio of 3:2) and 0.5 parts of reactive dye, stir for 20 minutes; pour it into a mold and cure it at 80°C for 2 days; let it stand at room temperature for 5 days to obtain a 0.2mm intermediate film;
[0047] Step 2: Soak the interlayer in toluene for 8 hours, transfer it to methanol and soak it for 4 hours; dry it at room temperature for 4 days to obtain a modified interlayer;
[0048] Step 3: Place the modified interlayer film between two layers of glass, set the temperature to 140°C, the pressure to 0.5 MPa, and perform hot pressing for 5 minutes to obtain high-strength laminated glass.
[0049] Comparative Example 3: A method for preparing high-strength laminated glass based on an intermediate film, increasing the amount of reactive anti-ultraviolet agent and starch nanoparticles introduced; specifically comprising the following steps:
[0050] Step 1: 18 parts of polytetramethylene glycol and 4 parts of reactive UV inhibitor were added to N, N-dimethylformamide in sequence; under nitrogen atmosphere, 12 parts of isophorone diisocyanate and 0.8 parts of organic tin catalyst were added in sequence; the temperature was raised to 85°C for reaction for 2 hours; vacuum degassing was performed; a starch dispersion containing 3 parts of starch nanoparticles (3wt% starch nanoparticles, 0.05wt% photoinitiator benzoin dimethyl ether, and the rest was N, N-dimethylformamide) was added, and the light irradiance was 40mW / cm 2Under ultraviolet light, stir for 20 minutes; add 1.8 parts of chain extender (1,4-butanediol and 2,6-pyridine dimethanol with a mass ratio of 3:2) and 0.5 parts of reactive dye, stir for 20 minutes; pour it into a mold and cure it at 80°C for 2 days; let it stand at room temperature for 5 days to obtain a 0.2mm intermediate film;
[0051] Step 2: Soak the interlayer in toluene for 8 hours, transfer it to methanol and soak it for 4 hours; dry it at room temperature for 4 days to obtain a modified interlayer;
[0052] Step 3: Place the modified interlayer film between two layers of glass, set the temperature to 140°C, the pressure to 0.5 MPa, and perform hot pressing for 5 minutes to obtain high-strength laminated glass.
[0053] Comparative Example 4: A method for preparing high-strength laminated glass based on an intermediate film, without modifying the intermediate film; specifically comprising the following steps:
[0054] Step 1: 20 parts of polytetramethylene glycol and 2 parts of reactive UV inhibitor were added to N, N-dimethylformamide in sequence; 12 parts of isophorone diisocyanate and 0.8 parts of organic tin catalyst were added in sequence under nitrogen atmosphere; the temperature was raised to 85°C for reaction for 2 hours; vacuum degassing was performed; 1.2 parts of starch dispersion containing starch nanoparticles (1.2wt% starch nanoparticles, 0.05wt% photoinitiator benzoin dimethyl ether, and the rest N, N-dimethylformamide) were added, and the light irradiance was 40mW / cm 2 Under ultraviolet light, stir for 20 minutes; add 1.8 parts of chain extender (1,4-butanediol and 2,6-pyridine dimethanol with a mass ratio of 3:2) and 0.5 parts of reactive dye, stir for 20 minutes; pour it into a mold and cure it at 80°C for 2 days; let it stand at room temperature for 5 days to obtain a 0.2mm intermediate film;
[0055] Step 2: Place the interlayer film between the two layers of glass, set the temperature to 140°C, the pressure to 0.5 MPa, and perform hot pressing for 5 minutes to obtain high-strength laminated glass.
[0056] Performance test 1: The interlayer films prepared in the embodiments and comparative examples were subjected to performance tests; the tensile performance was tested with reference to GB / T1040.3, and the tensile strength was tested at a rate of 50 mm / min; the bonding performance was tested with reference to GB / T33334, and the bonding strength was tested at a speed of 5 mm / min; the ultraviolet radiation resistance was tested with reference to the test method of GB15763.1, and the test was performed for 100 hours to observe the appearance; and the corresponding high-strength laminated glass was subjected to impact resistance test, and the test parameters were: the ball was dropped at a falling ball mass of 50 g and a height of 110 cm, and the obtained data were shown in the following table:
[0057]
[0058] It can be seen from the data in the above table that the present application uses polyurethane as the main body to prepare the intermediate film, and introduces reactive UV inhibitors, nano-starch particles, and subsequent solvent treatment to prepare a high-strength laminated glass with excellent UV resistance and impact resistance.
[0059] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing high-strength laminated glass based on an intermediate film, characterized in that: The following steps are involved: Step 1: Add polytetramethylene glycol and reactive UV-resistant agent to N,N-dimethylformamide in sequence; add diisocyanate and organotin catalyst in sequence under nitrogen atmosphere; heat to 80-85°C for reaction for 2-3 hours; vacuum degassing; add starch dispersion containing starch nanoparticles, stir for 20-30 minutes under ultraviolet light; add chain extender and reactive dye, stir for 20-30 minutes; pour into a mold, cure at 75-85°C for 1.5-2.5 days; let stand at room temperature for 4-6 days to obtain an intermediate film; Step 2: Soak the interlayer in toluene for 6 to 10 hours, transfer to methanol and soak for 2 to 4 hours; dry at room temperature for 3 to 5 days to obtain a modified interlayer; Step 3: Place the modified interlayer film between two layers of glass and heat-press them to obtain high-strength laminated glass; The raw materials of the intermediate film include the following components: by weight, 18 to 22 parts of polytetramethylene glycol, 2 to 3 parts of reactive UV inhibitor, 11 to 13 parts of diisocyanate, 0.5 to 1 part of organic tin catalyst, 1 to 1.5 parts of starch nanoparticles, 1 to 2 parts of chain extender, and 0.5 to 1 part of reactive dye; The preparation method of the reactive UV inhibitor is as follows: (1) uniformly stirring citric acid, cysteine and deionized water, stirring at 75-80°C for 2-2.5 hours; transferring to a blast oven, drying at 130-140°C for 10-12 hours to obtain pyridone diacid; (2) uniformly mixing pyridone diacid, epichlorohydrin and tetrabutylammonium bromide, stirring at 80-85°C for 20-30 minutes; cooling to 45-50°C, adding sodium hydroxide solution dropwise, stirring for 20-30 minutes; heating to 52-55°C and stirring for 4-6 hours to obtain diepoxy pyridone; (3) sequentially adding diepoxy pyridone and 2-(vinyloxy)ethylamine to toluene, reacting at 60-65°C for 6-8 hours, and evaporating toluene to obtain the reactive UV inhibitor.
2. The method for preparing high-strength laminated glass based on an intermediate film according to claim 1, characterized in that: The mass ratio of the citric acid, cysteine and deionized water is 19:(12-15):(10-20); the mass ratio of the pyridone diacid and epichlorohydrin is 3:(20-22); the molecular weight of the diepoxy pyridone and 2-(vinyloxy)ethylamine is 4:(2.8-3).
3. The method for preparing high-strength laminated glass based on an intermediate film according to claim 1, characterized in that: The starch dispersion comprises the following raw materials: 1-1.5 wt% starch nanoparticles, 0.05-0.08 wt% photoinitiator, and the rest is N,N-dimethylformamide.
4. The method for preparing high-strength laminated glass based on an intermediate film according to claim 1, characterized in that: The preparation method of the starch nanoparticles is as follows: (1) mixing thioglycolic acid, acetic anhydride and corn starch uniformly, adding sulfuric acid, stirring and reacting at room temperature for 12 to 16 hours; washing and drying to obtain thiolated starch; (2) dispersing corn starch and thiolated starch in a mass ratio of 4:1 in deionized water in turn to obtain a solution with a solid content of 5 to 6 wt %; stirring the solution at 90 to 92° C. for 1 to 1.5 hours, setting the power to 550 to 600 W for ultrasonic treatment for 10 to 15 minutes; centrifuging and taking the supernatant; (3) setting the power of ultrasonic waves to 550 to 600 W in an ice bath, transferring the supernatant to anhydrous ethanol at a rate of 2 to 5 mL / min, centrifuging and drying to obtain starch nanoparticles.
5. The method for preparing high-strength laminated glass based on an intermediate film according to claim 1, characterized in that: The chain extender includes 1,4-butanediol and 2,6-pyridine dimethanol in a mass ratio of 3:
2.
6. The method for preparing high-strength laminated glass based on an intermediate film according to claim 1, characterized in that: The process conditions of the ultraviolet irradiation are as follows: the light irradiance is 20 to 50 mW / cm 2 .
7. The method for preparing high-strength laminated glass based on an intermediate film according to claim 1, characterized in that: The temperature of the hot pressing compound is 120-140° C., the pressure is 0.4-0.6 MPa, and the time is 3-8 minutes.
8. The high-strength laminated glass prepared by the method for preparing high-strength laminated glass based on an intermediate film according to any one of claims 1 to 7, characterized in that: In the high-strength laminated glass, the thickness of the intermediate film is 0.2±0.05 mm.
Citation Information
Patent Citations
High-performance photochromic safe laminated glass and preparation method thereof
CN115723397A
Intermediate film with self-repairing function for laminated glass and processing technology of intermediate film
CN117925175A